Problematika Dalam Pembelajaran Berbasis Virtual Learning Environment (VLE) Terhadap Siswa dan Guru SMA/MA Pada Materi Biologi Di Masa COVID-19 - Tomi Apra Santosa; Lufri Lufri; Zulyusri Zulyusri (Journal on Education, 2021)
The research aims to find out the problem of Learning based on Virtual Learning Environment (VLE) for high school / MA students in biological materials in the COVID-19 era. This research is qualitative research with a fenomenology approach. Data collection techniques in research are observations, interviews, and questionnaires. The technique of ensuring the validity of data is triangulation. Data analysis techniques are data reduction, data presentation, and data verification. The results of the study can be concluded that SMA Negeri 12 Kerinci students have difficulty in understanding the concepts and learning materials and teachers has difficulty in practicing and evaluating learning outcomes, SMA Negeri 4 Kerinci students lack motivation and participation in learning and teachers have difficulty in making teaching materials, and MAS Koto Rendah students often experience internet network disruptions, students are less active in learning, and students have low motivation to learn virtually and teachers have difficulty in making teaching materials and explaining materials.